Implementation of Multicultural Education through the P7 Program with the Bhinneka Tunggal Ika Theme as an Effort to Strengthen Tolerant Attitudes at SMAN 3 Mataram - Hijrianti Hijrianti; Igatun Haniah; Hera Sukma Rahmaniah; Hulfayatullayli Hulfayatullayli; Ida Sugiastutik; Sawaludin Sawaludin (Penerbit Hellow Pustaka, 2026)
This study aims to examine the process of implementing multicultural education through the P7 Program with the theme Bhinneka Tunggal Ika as an effort to strengthen students’ tolerance attitudes at SMAN 3 Mataram, as well as to identify the supporting and inhibiting factors in its implementation. This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation. The research subjects consisted of P7 Program supervisors at SMAN 3 Mataram and representatives of students from grades 10, 11, and 12. The results of observations at SMAN 3 Mataram indicate that: (1) the implementation of multicultural education through the P7 Program was carried out in three stages, namely (a) planning, (b) implementation, and (c) evaluation. Overall, these stages were conducted with thorough preparation. (2) Supporting factors included (a) collaboration between teachers and students, (b) adequate facilities, and (c) the availability of school funding. Meanwhile, inhibiting factors included (a) a lack of collaboration among students and (b) low active participation from some students. (3) The impacts of the implementation were reflected in two aspects: (a) the cognitive aspect, including the development of students’ interests and talents and the improvement of students’ literacy skills, and (b) the affective aspect, including the growth of tolerance, mutual respect, strengthened social relationships, and increased cooperation among students. Overall, the P7 Program with the theme Bhinneka Tunggal Ika at SMAN 3 Mataram has proven effective as a means of strengthening multicultural education and fostering tolerance attitudes in the school environment.